2022
DOI: 10.1186/s12974-022-02504-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation of the splenic nerve bundle ameliorates dextran sulfate sodium-induced colitis in mice

Abstract: Background Vagus nerve stimulation has been suggested to affect immune responses, partly through a neuronal circuit requiring sympathetic innervation of the splenic nerve bundle and norepinephrine (NE) release. Molecular and cellular mechanisms of action remain elusive. Here, we investigated the therapeutic value of this neuromodulation in inflammatory bowel disease (IBD) by applying electrical splenic nerve bundle stimulation (SpNS) in mice with dextran sulfate sodium (DSS)-induced colitis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 66 publications
2
12
0
Order By: Relevance
“…Previous studies of LPS endotoxemia report considerable variability in TNF inhibition in response to VNS or SpNS [12,35,54]. Accordingly, we found that the same intensity of SpNS produces a wide range of TNF responses in animals injected with LPS (Fig.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Previous studies of LPS endotoxemia report considerable variability in TNF inhibition in response to VNS or SpNS [12,35,54]. Accordingly, we found that the same intensity of SpNS produces a wide range of TNF responses in animals injected with LPS (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…4C). In a study by Brinkman et al [12], most of the animals receiving splenic nerve stimulation had TNF values close to those of the sham-stimulated group (~ 6000 pg/mL vs. ~7500 pg/mL, respectively). The results from our study, which used similar stimulation parameters, suggest that in the Brinkman et al study it is likely that in a subset of animals that showed smaller TNF suppression, Q o may have been similarly high.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…For instance, splenectomy greatly reduces the early increases in plasma TNF‐α induced by endotoxaemia. Splenic nerve stimulation suppresses the release of TNF‐α in an animal model of inflammatory bowel disease (Brinkman et al., 2022). However, even though splenic nerve activity is elevated during endotoxaemia (Martelli et al., 2014), denervation of the spleen does not change TNF‐α or IL‐10 levels in the bloodstream (McKinley et al., 2022).…”
mentioning
confidence: 99%